The effect of temperature on bubble lattice formation in copper under in situ He ion irradiation. (1st April 2017) - Robinson, Aidan M; Edmondson, Philip D; English, Colin; Lozano-Perez, Sergio; Greaves, Graeme; Hinks, Jonathan A; Donnelly, Stephen E; Grovenor, Chris R M
Abstract: In situ ion irradiation in a transmission electron microscope was used to investigate the effects of temperature on radiation-induced bubble lattice formation in Cu by low energy (12 keV) helium ions. Bubble lattices were observed to form between − 100 and 100 °C, but at 200 °C lattice formation was impeded by continued growth and agglomeration of bubbles. Both nucleation of bubbles, and to a lesser extent bubble lattice formation, are observed at lower fluences as temperature increases, which we suggest is due to increased point defect mobility. Previous work on point defect concentrations in irradiated copper is considered when interpreting these results. Graphical abstract: Bubble arrays and inset FFTs from the same sample implanted at 100 °C to (a) 3.59 × 10 16 ions/cm 2 showing an amorphous bubble array and then (b) at 6.33 × 10 16 ions/cm 2 where a lattice has formed.